Enhanced Electrochemical Performances of Mn3O4/Heteroatom-Doped Reduced Graphene Oxide Aerogels as an Anode for Sodium-Ion Batteries - Nor Fazila Mahamad Yusoff; Nurul Hayati Idris; Muhamad Faiz Md Din; Siti Rohana Majid; Noor Aniza Harun (Nanomaterials, 2022)
Owing to their high theoretical capacity, transition-metal oxides have received a considerable amount of attention as potential anode materials in sodium-ion (Na-ion) batteries. Among them, Mn3O4 has gained interest due to the low cost of raw materials and the environmental compatibility. However, during the insertion/de-insertion process, Mn3O4 suffers from particle aggregation, poor conductivity, and low-rate capability, which, in turn, limits its practical application. To overcome these obstacles, we have successfully prepared Mn3O4 nanoparticles distributed on the nitrogen (N)-doped and nitrogen, sulphur (N,S)-doped reduced graphene oxide (rGO) aerogels, respectively. The highly crystalline Mn3O4 nanoparticles, with an average size of 15–20 nm, are homogeneously dispersed on both sides of the N-rGO and N,S-rGO aerogels. The results indicate that the N-rGO and N,S-rGO aerogels could provide an efficient ion transport channel for electrolyte ion stability in the Mn3O4 electrode. The Mn3O4/N- and Mn3O4/N,S-doped rGO aerogels exhibit outstanding electrochemical performances, with a reversible specific capacity of 374 and 281 mAh g−1, respectively, after 100 cycles, with Coulombic efficiency of almost 99%. The interconnected structure of heteroatom-doped rGO with Mn3O4 nanoparticles is believed to facilitate fast ion diffusion and electron transfer by lowering the energy barrier, which favours the complete utilisation of the active material and improvement of the structure’s stability.